Understanding novel gap-bridged remote laser welded (RLW) joints for automotive high-rate and temperature applications. (15th January 2021) - Das, Abhishek; Masters, Iain; Williams, David
Highlights: Three part-to-part 'gap-bridged' Remote Laser Welded (RLW) joints were evaluated for microstructure, high-rate and temperature-dependent tensile behaviours. 'Good-welds' were quantified for tensile performance from moderate (0.1 m/s) to high-speed (10 m/s) at room temperature and fracture strains were obtained in between 0.21 to 0.25 for all gap and speed conditions. The effects of temperature on the RLW fillet edge welds from depressed (-50°C) to elevated values (up to 300°C) were evaluated. Actual fusion zone based finite element simulations of the RLW joints were developed using the Johnson-Cook material failure model to predict joint strength. Abstract: This paper investigates the microstructure, high-rate and temperature dependent tensile behaviour of fillet edge joints produced by novel 'gap-bridged' remote laser welding (RLW) using an automotive grade aluminium alloy AA6014, commercially known as AC-170PX, extensively used for automotive skin panel applications. Three part-to-part gap-bridged RLW fillet edge welds, produced with different gaps (0.2 mm, 0.4 mm and 0.6 mm) were examined for joint geometry and microstructure. Relatively larger columnar grains resulting from directional solidification were observed in the fusion zone and microhardness was reduced by 15- 20% due to precipitates disappearance. Moderate (0.1 m/s) to high speed rate (10 m/s) tensile tests performed at room temperature ( 23°C) were used to determine high-rate tensile performance. Although the strain rate dependency was found to be low, an increase in tensile extension was obtained. Additionally, the joint tensile performance was evaluated over a range of temperatures between -50°C and 300°C. Using digital image correlation (DIC), fracture strains were obtained in the range from 0.21 to 0.25 for all gap and speed conditions. Fusion zone based finite element simulations were performed using the Johnson-Cook material failure model to predict joint strength. Additionally, the suitability of gap-bridged RLW joints for automotive applications was determined by comparison with two industrial joining methods, self-piercing riveting (SPR) and resistance spot welding (RSW). Graphical abstract: Image, graphical abstract